2013
DOI: 10.1142/s2010194513010313
|View full text |Cite
|
Sign up to set email alerts
|

OPTICAL AND DIELECTRIC PROPERTIES OF THE COBALT DOPED TiO2 NANOPARTICLES

Abstract: Cobalt doped Titanium Dioxide (TiO 2 ) were synthesized by a standard solid-state reaction method. The dielectric constant and loss have been measured as a function of frequency (100 Hz-1 KHz) and temperature (50°C to 300°C). Similar behavior is observed between dielectric constant and dielectric loss. Both dielectric constant and dielectric loss are found to decrease with increasing frequency. Photoluminescence (PL) spectra were taken at different excitation wavelength. PL emission spectra shows a broad spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It is observed that at low frequency, the dielectric constant is large for both specimens and gradually decreases with an increase in frequency and this behavior is in agreement with a previous report. 36 Properties like space charge, electronic, ionic, and dipolar polarizations affect the dielectric properties of the material. The higher dielectric constant values at lower frequencies may be due to the simultaneous presence of interfacial polarization in all specimens.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that at low frequency, the dielectric constant is large for both specimens and gradually decreases with an increase in frequency and this behavior is in agreement with a previous report. 36 Properties like space charge, electronic, ionic, and dipolar polarizations affect the dielectric properties of the material. The higher dielectric constant values at lower frequencies may be due to the simultaneous presence of interfacial polarization in all specimens.…”
Section: Resultsmentioning
confidence: 99%
“…2; The graphic in the Figure 3 was drawn with the square root of the variation of the capacitor weight in the vertical axis and the voltage applied in the horizontal axis in order to better observe the variation of curve (anamorphosis). The phenomenon can be associated to the variation of the dielectric constant when the frequency increases, as reported in the case of TiO 2 (Mangrola, Joshi, Parmar, & Pillai, 2013). In fact, this oscillation observed in the curve deserves more investigation but the experimental range of voltage values from 13kV to 25kV are a little below the theoretical ones possibly because of the usual (Murata Innovator in Electronics, n.d.; Maxim Integrated Tutorials, n.d., Vishay Sprague Report, n.d.) reduction of the capacitance according to the voltage applied increasing for an arbitrary dielectric substance.…”
Section: Resultsmentioning
confidence: 74%
“…A graphitic carbon reflection at a 2θ of 23° was observed in the samples after annealing, which was presumably derived from the calcination of the organic linker at 400 °C. , There were no impurity peaks in the patterns of Co-doped TiO 2 when compared with those of pure TiO 2 , implying that the doping with Co 2+ ions did not change the original TiO 2 structure. However, the peak positions shifted slightly to the left owing to the presence of the dopant, indicating the substitution of Co 2+ ions in the TiO 2 lattice. , Moreover, the increase in peak sharpness and intensity that was observed in the pattern of the Co-doped TiO 2 implies an enhancement of crystal growth. The crystalline sizes of the TiO 2 and Co-doped TiO 2 particles were estimated to be 9 and 10 nm, respectively, by using the Debye–Scherrer equation with the width of the (101) planes.…”
Section: Results and Discussionmentioning
confidence: 94%